Strategies for Successful Transition into Mainstream Schools for Young Children with Autism Spectrum Disorders: A Case Study - Mardiyanti, Mardiyanti (Department of Nursing, Faculty of Medicine, Diponegoro University, 2016)
Background: Meeting changes can be very problematic for children with Autism Spectrum Disorders (ASDs) whereas other children may take it for granted. As a result,they may cry, get upset, scream, do hand flapping or even self-harming that shows their inability to cope with the changes and their preference of sameness and routine activities. To understand the issue of changes in children with autism, people should know the complexity of the disorders.Purpose: This article will explain further about the strategies for a successful transition into mainstream schools for young children with autism as illustrated in Jack’s case study in the appendices.Methods: A case study was conducted to one respondent. Firstly, the article will explain ASDs and its atypical characteristics of 6-years old Jack. Then it will discuss strategies to help Jack’s transition process, as well as strategies to support his learning process during schooling which finally comes up with a conclusion to support Jack and his family’s transition into mainstream primary education.Results: Strategies for successful transition into mainstream schools for young children with autism include using visual information and activity schedules, managing sensory overload, and building literacy skills.Conclusion: Attractive playing can be effective strategies to build skills for successful transition of young children with autism.